ANALYSIS OF THE NEEDS FOR INTERACTIVE MULTIMEDIA DEVELOPMENT FOR SCIENCE AND SOCIAL STUDIES - Kelwarany, Mera; H, Nurhikmah; Lu’mu, M. Pd, Lu'mu (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2024)
This study examines the use of interactive multimedia in teaching Natural and Social Sciences (IPAS) at SD Negeri Kompleks IKIP 1 Makassar. Within the 2023/2024 Independent Curriculum framework, this research aims to enhance student interactivity and understanding using the Smart Apps Creator (SAC) application. A mixed-methods approach, including surveys, unstructured interviews, and document analysis, was employed from November 2023 to January 2024. The findings indicate that conventional methods, such as textbooks and slide presentations, are less effective in facilitating independent and interactive learning. Using SAC, through visualisation, animation, and simulation, increased student engagement and motivation and helped clarify abstract concepts such as energy. This study underscores the importance of interactive multimedia in enriching students' learning experience and highlights the need for teacher training to optimise the use of this technology.